2012
DOI: 10.1016/j.neulet.2012.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Orexin A decreases lipid peroxidation and apoptosis in a novel hypothalamic cell model

Abstract: Current data support the idea that hypothalamic neuropeptide orexin A (OxA; hypocretin 1) mediates resistance to high fat diet-induced obesity. We previously demonstrated that OxA elevates spontaneous physical activity (SPA), that rodents with high SPA have higher endogenous orexin sensitivity, and that OxA-induced SPA contributes to obesity resistance in rodents. Recent reports show that OxA can confer neuroprotection against ischemic damage, and may decrease lipid peroxidation. This is noteworthy as independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 48 publications
2
48
1
Order By: Relevance
“…Evidence strongly links development of AD and PD with oxidative stress and mitochondrial dysfunction in the brain (Agostinho et al, 2010; Ferreiro et al, 2012; Niranjan, 2013). In recent in vitro and in vivo studies, we and others have shown that orexin is neuroprotective, reducing neuronal damage caused by ischemia or oxidative insult in hypothalamic, hippocampal, and cortical tissue (Butterick et al, 2012; Sokolowska et al, 2012; Yuan et al, 2011). While the mechanism is not fully defined, orexin appears to increase resistance to oxidative stress by upregulation of hypoxia-inducible factor 1 alpha (HIF-1α) (Butterick et al, 2013; Feng et al, 2014; Sikder and Kodadek, 2007; Yuan et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Evidence strongly links development of AD and PD with oxidative stress and mitochondrial dysfunction in the brain (Agostinho et al, 2010; Ferreiro et al, 2012; Niranjan, 2013). In recent in vitro and in vivo studies, we and others have shown that orexin is neuroprotective, reducing neuronal damage caused by ischemia or oxidative insult in hypothalamic, hippocampal, and cortical tissue (Butterick et al, 2012; Sokolowska et al, 2012; Yuan et al, 2011). While the mechanism is not fully defined, orexin appears to increase resistance to oxidative stress by upregulation of hypoxia-inducible factor 1 alpha (HIF-1α) (Butterick et al, 2013; Feng et al, 2014; Sikder and Kodadek, 2007; Yuan et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Work with these animal models has clearly defined a direct link between orexin signaling and neuromodulation of SPA; however, the cellular signaling pathways through which orexin mediates SPA and obesity resistance still remain largely unknown [9,38]. We present here evidence from multiple in vitro investigations, including data from our ongoing work and that from other non-orexin focused rodent models, to delineate potential mechanisms through which orexin might affect obesity resistance.…”
Section: Orexin and Obesity Resistancementioning
confidence: 99%
“…While increases in HIF-1α are usually associated with hypoxia, OXA induction of HIF-1α occurs in normal, non-hypoxic hypothalamic tissue [70]. OXA has been shown to be neuroprotective in cerebral cortex and in hypothalamic cell culture following oxidative stressors [71,38], potentially through activation of HIF-1α. Recent studies have shown that in conjunction with MAPK, PGC-1α is important in regulating HIF-1α expression [72,62,73,61].…”
Section: Orexin-mediated Signaling and Energy Balancementioning
confidence: 99%
See 1 more Smart Citation
“…At 80 -90% confluence, cells were synchronized overnight in serum-free medium and treated with human recombinant orexin A or B (0, 10 and 100 nM) (Interchim, Montlucon, France) for 24 h. Untreated cells were used as control. The dose and duration of treatments were chosen on the basis of pilot and previous published experiments (12,62,63). QM7 cells were washed twice with phosphate-buffered saline (PBS 1ϫ) and incubated for 12 h in medium with brefeldin A (0.3 g/ml), and lysates and medium were subjected to immunoblot analysis.…”
Section: Methodsmentioning
confidence: 99%